Strategic change management: Change management challenges in the Danish police reform - Rex Degnegaard (Copenhagen Business School (CBS), 2010)
Since its commencement in January 2007, the Danish police reform has been a hot topic in the media, at universities, dinner parties, and in waiting rooms. The general perception of the police reform is that it is a failure. During 2008, the reform has been subject to much public debate, which has linked many unfortunate cases of police neglect with the police reform. Furthermore, the public debate has created a picture of a police not in control and with the reform to blame. Given this troublesome context of the police reform, the question which everyone is asking is: why did it go wrong? Along with the question of: whose fault was it? The current thesis does not provide one single answer to the chaotic situation surrounding the police reform. Neither does it place the responsibility of the unforeseen consequences of the police reform. Rather, this thesis focuses on unforeseen consequences of the reform in regards to change management and organizational implications. This thesis is submitted as a doctoral thesis at Copenhagen Business School in completion of a three-year Ph.D. study. The thesis is the result of a longitudinal research study on change management challenges in the Danish police reform. The study rests on a multi-sited methodology compromising an array of research methods such as interviews, field studies, presentations, meetings, written document studies, etc. over the course of the three years' duration of the study. The study draws from different strands of literature, primarily change management literature and institutional literature, including resource dependency theory. The research question, which guides the thesis, is as follows: What are the change management challenges and the organizational implications of introducing a reform, which has a functional-rational logic of modernization and efficiency to the Danish police, which is a strongly institutionalized organization? The research question has been answered through the analysis, which is divided into three sections: - Change management in the reform, - Content of the police reform, and - The external control of the police.
hdl:10398/8008
Keywords: 650